The role of the military in the Arab uprisings: the cases of Tunisia and Libya - Sarihan, Ali (2016)
This thesis examines the role of the military in Tunisia and Libya during the 2010-2011 Arab uprisings by asking why the two states’ military forces chose to either defect from or defend the ruling administration. Using a comparative case study methodology, this study demonstrates that the joint configuration of energy capacity, military structure and the strength of protests led to the different outcomes in these two cases. The data indicates that one can understand the impact of these three factors using theories that focus on the correlation between rational action, institutional identity, economic inducements, and ideological stances. Thus, I employed approaches from rational choice and institutionalism as the theoretical framework for this study. This study shows that the actions of the Tunisian and Libyan military forces should be read through this theoretical framework. While informative, conclusions drawn from these cases do not allow for universal generalizations. Additionally, it is important to note that the three influential factors are not the only elements that influenced the variations in outcome during the Tunisian and Libyan conflicts. Moreover, I do not make a comparison in terms of the absolute values of the factors, but rather in terms of relative values.